Hubungan antara Prokrastinasi Akademik dengan Kecemasan Akademik pada Mahasiswa Mengerjakan Tugas Akhir di Universitas Muhammadiyah Sidoarjo - Daffa Naufali Pratama; Eko Hardi Ansyah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research is based on the phenomenon of academic procrastination found in final students of Universitas Muhammadiyah Sidoarjo. Academic procrastination is task avoidance caused by feelings of displeasure with the task and fear of failing to complete the task. One of the factors that trigger academic procrastination is academic anxiety. The academic anxiety variable was measured using the academic anxiety scale adopted from Ridwan with a validity coefficient value moving from 0.926 -0.746 and an alpha reliability coefficient (α) value of 0.907. The academic procrastination variable was measured by the academic procrastination scale in completing the thesis adapted from Rahayu. with a validity coefficient value moving from 0.094 to 0.596 and with an alpha (α) reliability coefficient value of 0.858. The correlation between variables was analyzed using Spearman's Rho correlation test with the help of JASP 19.0 software. The results showed that there was a relationship between the two variables with a correlation coefficient (r) of 0.703 with a significance (p) of 0.001 (<0.05).